2004
DOI: 10.1099/mic.0.27403-0
|View full text |Cite
|
Sign up to set email alerts
|

A calcium signal is involved in heterocyst differentiation in the cyanobacterium Anabaena sp. PCC7120

Abstract: The impact of calcium signals in virtually all cells has led to the study of their role in prokaryotic organisms as stress response modulators. Cell differentiation in adverse conditions is a common Ca2+-requiring response. Nitrogen starvation induces the differentiation of N2-fixing heterocysts in the filamentous cyanobacterium Anabaena sp. PCC7120. This paper reports the use of a recombinant strain of this organism expressing the photoprotein aequorin to monitor the intracellular free-calcium concentration d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
49
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(52 citation statements)
references
References 47 publications
3
49
0
Order By: Relevance
“…The model also assumed that protons constitute the counter ions exchanged for calcium to maintain charge. The concentrations of Ca 2+ i attained during transport, which are of paramount importance for cell physiology, given the ion's toxicity in most cellular systems, including cyanobacteria (14,15), remain unknown, but there is a potential that a borer's cells might experience prolonged, very high Ca 2+ i concentrations (10). The experimental evidence in support of the current model was obtained using selective inhibitors and an extracellular calcium fluorophore to study Ca 2+ dynamics during boring.…”
supporting
confidence: 50%
“…The model also assumed that protons constitute the counter ions exchanged for calcium to maintain charge. The concentrations of Ca 2+ i attained during transport, which are of paramount importance for cell physiology, given the ion's toxicity in most cellular systems, including cyanobacteria (14,15), remain unknown, but there is a potential that a borer's cells might experience prolonged, very high Ca 2+ i concentrations (10). The experimental evidence in support of the current model was obtained using selective inhibitors and an extracellular calcium fluorophore to study Ca 2+ dynamics during boring.…”
supporting
confidence: 50%
“…The detection of a transient increase of [Ca 2ϩ ] i during heterocyst differentiation (29) and the results obtained with manipulation of extracellular Ca 2ϩ concentrations (9) suggested that Ca 2ϩ might be a signal for the differentiation process. In this report, we describe a Ca 2ϩ -binding protein, CcbP, from Anabaena 7120 and suggest a role of CcbP in regulation of heterocyst differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…This may also explain how reprecipitation at the lagging end may cause microbial borers to act as cements agent in sedimentary structures when growth allows them to cross between mineral grains (27). Our model also opens biological questions as to how boring cyanobacteria might cope with altered intracellular Ca 2+ , which is otherwise kept low and tightly regulated (22). Because a lowering of ocean calcium carbonate saturation state driven by anthropogenic CO 2 emissions (28) will lower the bioenergetic cost of boring, a global increase in cyanobacterial bioerosion rates in shallow waters can be logically predicted, an outcome for which some experimental evidence is already available (29), likely affecting already impacted (30) coral reefs, as well as the bivalve fisheries industry (7).…”
Section: +mentioning
confidence: 97%
“…Intense extrusion of intracellular Ca 2+ by P-type ATPases strategically anchored on the plasma membrane of the distal cells, close to the borehole entrance, keep intracellular concentrations within the typical physiological micromolar (22) range and establish an intracellular diffusive mass transport down the concentration gradient that brings Ca 2+ along the trichome toward this region. Either through active transport with additional ATPases located at the cross walls, or through channels that allow facilitated diffusion of Ca 2+ and protons (the first variant is depicted in Fig.…”
Section: +mentioning
confidence: 99%